Overcoming the Fear of the "Other": Building Trust Between British Muslims and the Wider Community. Issue 4 (2nd October 2017) - Knox, Emily; Latif, Asam; Mohammadian, Somaiyeh; Malik, Abida; Hussain, Musharraf
Abstract: Initiatives that seek to build community trust are timely given the increasing focus on terror-related attacks and the rise in associated hate crimes as well as scrutiny of the way Muslim leadership is responding to such incidents. This paper details a novel and proactive model that aims to improve and build trust between Muslims and the wider community. The Trust Building Project was found to accomplish its two objectives. Not only was there an improvement in participant knowledge of Islam scores but there was also evidence suggesting trust had improved through engagement, understanding and through getting to know one another. Listening and learning sought to dispel myths and highlight shared morals and values. We propose that through these interactions the basis to building a more trusting society can be formed. It is unclear to what extent this could reduce incidents of hate crime and discrimination, however social change has been shown to occur where there are grass roots initiatives and suggestions are made to examine how this work can be rolled out nationally in order to address the trust deficit seen within our society today.